14.6k views
1 vote
Find the solution to the equation 4r + 2(r - 8) = 4(3 + r).

2 Answers

0 votes

Answer:

r = 14

Explanation:

4r + 2(r - 8) = 4(3 + r)

4r + 2r - 16 = 12 + 4r

6r - 16 = 12 + 4r

6r - 4r - 16 = 12 + 4r - 4r

2r - 16 = 12

2r - 16 + 16 = 12 + 16

2r = 28

2r ÷ 2 = 28 ÷ 2

r = 14

User Abbey
by
5.9k points
1 vote

Answer:

r = 14

Explanation:

Use distributive property:

4r + 2r - 16 = 12 + 4r

Combine like terms:

6r - 16 = 12 + 4r

Isolate the variable:

6r = 28 + 4r

2r = 28

r = 14

User Lykos
by
5.2k points